Fist fight [videorecording (DVD)] - Morgan, Tracy, 1968-; Ice Cube (Musician); Day, Charlie ([Publisher not identified], 2017)
On the last day of high school, mild-mannered English teacher Andy Campbell tries to keep it together amidst senior pranks, a dysfunctional administration, and budget cuts that put jobs on the line. Then he accidentally crosses his much tougher and deeply feared colleague, Ron Strickland, who challenges Campbell to an old-fashioned throw down. News of the fight spreads like wildfire and it ends up becoming the very thing the school, and Campbell, needs.